Exploring the moderating effect of children's nutritional knowledge on the relationship between product evaluations and food choice. (January 2016) - Tarabashkina, Liudmila; Quester, Pascale; Crouch, Roberta
Abstract: Objective: Although the last decade has seen multiple attempts to increase consumers' nutritional knowledge in expectation that this will result in healthier diets, extant knowledge about the influence of nutritional knowledge on children's food choices remains scarce due to mixed empirical evidence and limited inquiry into the role of product evaluations on the consumption of less healthy foods. Furthermore, no research has examined whether nutritional knowledge can effectively moderate the relationship between product evaluations and food consumption, leaving a gap in our knowledge about potentially effective intervention strategies to curb childhood obesity. Method: Using survey data from children aged 7–13 years and their parents ( N  = 354) recruited at an annual fair visited by families in South Australia, regressions were performed to examine how product evaluations are associated with the consumption of less healthy foods and whether nutritional knowledge reduces the strength of these associations at different ages (7–8 years, 9–10 years, and 11–13 years). Results: While children did not view fast foods to be fun or healthy, there was a positive association between appealing taste, perceived social acceptability and consumption of less healthy foods. Higher nutritional knowledge weakened the relationship between product evaluations and consumption in children younger than 11. Parents with higher nutritional knowledge had children who tended to consume less healthy foods less frequently. Although older children (11–13 years) possessed higher nutritional knowledge, it was not associated with their consumption; instead, taste and perception of social acceptability were the only factors associated with frequent consumption of less healthy products. Conclusion: Practitioners are encouraged to test intervention strategies that concentrate on both product evaluations and nutritional knowledge to provide more effective outcomes. Further research about peer norms that endorse unhealthy eating is encouraged to facilitate a more comprehensive approach to unhealthy eating. Highlights: Taste, social appeal, and acceptability positively relate to food consumption. Children's nutritional knowledge reduces consumption of less healthy foods. Nutritional knowledge lessens the influence of social appeal and acceptability.